80TH ANNIVERSARY OF PROFESSOR OF MINERALOGY AND PETROLOGY DEPARTMENT OF THE PERM STATE UNIVERSITY IBLAMINOV R.G - Busygina, N. A. (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2022)
Brief information about academic and research activity of Professor of Mineralogy and Petrology Department of the Perm State University R.G. Iblaminov is presented